Evaluación del nivel de presión sonora y su relación en las otopatias ocupacionales en las estaciones de bombeo quillan 1 y quillan 2 de la empresa pública - empresa municipal de agua potable y alcantarillado - Ambato - sistema de prevención de ruido. - Rivas Gavilanes, Jorge Cristobal (2016)
The present research makes a noise study in the pumping station of Quillan 1 and Quillan 2 of the Public Company Empresa Municipal de Agua Potable y Alcantarillado Ambato to develop a Noise Prevention. The presence of Occupational Ear pathology were identified on operators with greater exposure to industrial noise using labor audiometry. Then most affected Risk Factors are then identified using the qualitative matrix from that considers the probability and consequence. For further investigation a study of sound pressure level is made regarding jobs in the pumping stations in Quillan 1 and Quillan 2. This study uses the engineering method according to the standard UNE-EN ISO 9612: 2009 taking into account the exposure of workplaces by test to determine the dose and level. The hypothesis tested in this study is that noise affects Occupational Ear pathology for job execution of pumping station Quillan 1 and Qullan 2. The deep of industrial noise determined that the risk factor partially intolerable for this system of work was the noise. The Noise Prevention System product of this work identified some control measures to the aspects set as high risk in terms of source controls in the middle and at the receiver.